Clinical criteria versus a possible research case definition in chronic fatigue syndrome/myalgic encephalomyelitis. Issue 2 (3rd April 2017) - Jason, Leonard A.; McManimen, Stephanie; Sunnquist, Madison; Newton, Julia L.; Strand, Elin Bolle
ABSTRACT: Background: The Institute of Medicine (IOM) recently developed clinical criteria for what had been known as chronic fatigue syndrome. Given the broad nature of the clinical IOM criteria, there is a need for a research definition that would select a more homogenous and impaired group of patients than the IOM clinical criteria. At the present time, it is unclear what will serve as the research definition. Purpose: The current study focused on a research definition which selected homebound individuals who met the four IOM criteria, excluding medical and psychiatric co-morbidities. Methods: Our research criteria were compared to those participants meeting the IOM criteria. Those not meeting either of these criteria sets were placed in a separate group defined by six or more months of fatigue. Data analyzed were from the DePaul Symptom Questionnaire and the 36-item Short-Form Health Survey (SF-36). Due to unequal sample sizes and variances, Welch's F tests and Games-Howell post-hoc tests were conducted. Results: Using a large database of over 1000 patients from several countries, we found that those meeting a more restrictive research definition were even more impaired and more symptomatic than those meeting criteria for the other two groups. Conclusion: Deciding on a particular research case definition would allow researchers to select more comparable patient samples across settings, and this would represent one of the most significant methodologic advances for this field of study.